2006
DOI: 10.1021/jm051147+
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Studies of a New Series of 5-Heteroarylcarbamoylaminopyrazolo[4,3-e]1,2,4-triazolo[1,5-c]pyrimidines as Human A3 Adenosine Receptor Antagonists. Influence of the Heteroaryl Substituent on Binding Affinity and Molecular Modeling Investigations

Abstract: Some pyrazolotriazolopyrimidines bearing different heteroarylcarbamoylamino moieties at the N5-position are described. We previously reported the synthesis of a water soluble compound with high potency and selectivity versus the human A3 adenosine receptor as antagonist, and herein we present an enlarged series of compounds related to the previously mentioned one. These compounds showed A3 adenosine receptor affinity in the nanomolar range and different levels of selectivity evaluated in radioligand binding as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…268 Subsequent studies have indicated that small substituents, such as a methyl group at the N 8 -position, an unsubstituted phenyl ring at the N 5 -position and a furyl ring at the 2-position, were crucial for hA 3 AR affinity, as confirmed by compound 143 (K i hA 3 AR 5 0.16 nM). [269][270][271][272] In order to improve water solubility, the N 5 -phenyl ring was later substituted with a pyridinium salt, as represented by compound 144 (water solubility 5 15 mM), which also significantly improved hA 3 AR affinity (K i hA 3 AR 5 0.01 nM). 273 Substitution of the N 5 -phenyl moiety with various N 5 -heteroaryl rings has resulted in a general loss of hA 3 AR affinity and selectivity.…”
Section: Nonxanthine Derivativesmentioning
confidence: 99%
“…268 Subsequent studies have indicated that small substituents, such as a methyl group at the N 8 -position, an unsubstituted phenyl ring at the N 5 -position and a furyl ring at the 2-position, were crucial for hA 3 AR affinity, as confirmed by compound 143 (K i hA 3 AR 5 0.16 nM). [269][270][271][272] In order to improve water solubility, the N 5 -phenyl ring was later substituted with a pyridinium salt, as represented by compound 144 (water solubility 5 15 mM), which also significantly improved hA 3 AR affinity (K i hA 3 AR 5 0.01 nM). 273 Substitution of the N 5 -phenyl moiety with various N 5 -heteroaryl rings has resulted in a general loss of hA 3 AR affinity and selectivity.…”
Section: Nonxanthine Derivativesmentioning
confidence: 99%
“…Additional studies suggested that involvement of the residue Tyr254 in a hydrogen bond with the pyridyl ring was responsible for both enhanced receptor affinity and selectivity (Tafi et al 2006). The replacement of the N 5 -pyridine moiety with several N 5 -heteroaryl rings produced a general loss of affinity and selectivity at the hA 3 AR (Pastorin et al 2006). …”
Section: A3ar Antagonistsmentioning
confidence: 99%
“…Many A 3 models have been published (see Table XII) describing the hypothesized interaction of many different ligands, at least 12 of them using bRh as a template. 73,74,76,79,[86][87][88][89]95,104,108,[112][113][114][115][116][117][118][119][120][121][122] As regards N 6 adenosine derivatives, the main models proposed hypothesize that ligands interact with TM3, TM5, TM6, TM7, and EL2.…”
Section: A 3 Receptor Modelsmentioning
confidence: 99%